Korelasi Antara Peningkatan Kemandirian Belajar Dengan Pemahaman Konsep Peserta Didik Pada Materi Koloid Menggunakan Model POGIL - Ade Paramitha Utari; Muhammad Hasan; Muhammad Adlim; Elisa (Postgraduate, University of Mataram, 2023)
Bland learning is one of the causes of students' inability to explore freely by prioritizing self-regulated in each learning process. The POGIL model is an approach that makes students free to explore every step of the learning process with the teacher serving as a helpful facilitator. This research aims to look at the correlation between increased self-regulated and conceptual understanding in colloidal material with the POGIL model. The increase that occurs does affect each other. The results in this study experienced an increase in conceptual understanding, with a mean of 70.09 in the experimental group and 51.21 in the control group. At the same time, the increase in the value of students' self-regulated was 84.59 in the in the experimental group and 72.37 in the control group. Pearson product-moment correlation analysis was obtained at -0.243. This study concludes that learning using the POGIL model effectively increases learning self-regulated and conceptual understanding. The correlation of these two variables is interpreted as a negative correlation or an indirect relationship (inverse).